Sleep and circadian rhythm disturbances: multiple genes and multiple phenotypes - Wulff, K; Porcheret, K; Cussans, E; Foster, R (Elsevier, 2009)
Sleep is regulated by two broad mechanisms: the circadian system, which generates 24-h rhythms of sleep propensity and a wake-dependent homeostatic sleep process whereby sleep pressure increases during wake and dissipates during sleep. These, in turn, regulate multiple brain structures and neurotransmitter systems. In view of the complexity of sleep it is not surprising that there is considerable variation between individuals in both sleep timing and propensity. Furthermore, marked abnormalities in sleep are commonly encountered in psychiatric and neurodegenerative disorders. Teasing apart the genetic versus environmental contributions to normal and abnormal sleep is complex. Here we attempt to summarise what recent progress has been made, and what will be needed in the future to gain a more complete understanding of this fundamental aspect of physiology.